2022
DOI: 10.1371/journal.pone.0264187
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial inclusion on open defecation and sharing of toilet facilities among households in Ghana

Abstract: Globally, and in Ghana, a lot of people do practice open defecation as well as share toilet facilities with other households. Meanwhile, open defecation in particular, is associated with numerous negative health and economic effects. To this end, a number of empirical studies have been conducted on the determinants of access to sanitation facilities among households in Ghana. Nonetheless, while financial inclusion (sustainable ways of ensuring easier accessibility to cheap and useful financial products and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…According to the results of the review, 17 articles (54.84%) examined the relationship between economic status and OD behavior, and 14 articles (82.35%) of them stated that there was a relationship between economic status and OD behavior. This study is also consistent with the results of a study in Ghana, which states that individuals with low economic levels are 0.62 times more likely to have OD compared to individuals with high economic levels [62]. The results of studies in other countries such as sub-Saharan Africa [25] and Nigeria [22] also mention that OD behavior tends to occur in people with low economic status.…”
Section: Economic Statussupporting
confidence: 90%
See 1 more Smart Citation
“…According to the results of the review, 17 articles (54.84%) examined the relationship between economic status and OD behavior, and 14 articles (82.35%) of them stated that there was a relationship between economic status and OD behavior. This study is also consistent with the results of a study in Ghana, which states that individuals with low economic levels are 0.62 times more likely to have OD compared to individuals with high economic levels [62]. The results of studies in other countries such as sub-Saharan Africa [25] and Nigeria [22] also mention that OD behavior tends to occur in people with low economic status.…”
Section: Economic Statussupporting
confidence: 90%
“…Economic status is a person's ability to meet needs in accordance with existing income and become one of the factors in facilitating behavior change [61]. Economic conditions affect the ability of individuals to provide sanitation facilities including the availability of latrines [62]. According to the results of the review, 17 articles (54.84%) examined the relationship between economic status and OD behavior, and 14 articles (82.35%) of them stated that there was a relationship between economic status and OD behavior.…”
Section: Economic Statusmentioning
confidence: 99%
“…Similar finding was reported by Edwards and Langpap 38 in Guatemala. Beyond choosing healthy energy sources, financial inclusion has been found to be associated with an enhancement in healthy solid waste disposal, 39 and a reduction in open defecation in Ghana 40 as well as an enhancement in access to basic drinking water in Africa. 34 The implication is that, financial inclusion enhances access to health inputs (such as healthy energy, and basic drinking water and sanitation), hence, it is not surprising that financial inclusion has been found to be associated with an improvement in population health in 33 African countries.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the effect of financial inclusion is not farfetched because, studies have revealed financial inclusion to enhance poverty alleviation, economic growth and net wealth benefits [ 22 – 25 ], hence, boosting the ability of people to afford healthy solid waste disposal methods which normally come at a fee. In Ghana, financial inclusion has been found to be negatively associated with open defecation and sharing of toilet facilities among households [ 33 ]. Similarly, financial inclusion has been found to increase access to basic drinking water and sanitation in Africa [ 34 ].…”
Section: Discussionmentioning
confidence: 99%